The Carpathians : Discovering the Highlands of Poland and Ukraine - Dabrowski, Patrice M., 1960- (Book collections on Project MUSE., 2021)
"A study of how three discrete mountain ranges within the Carpathian Mountain system -- the Tatras, Eastern Carpathians, and Bieszczady Mountains, together with their indigenous highlanders (Górale, Hutsuls, Boikos, and Lemkos)--were discovered and turned into popular tourist destinations by Poles and Ukrainians in the nineteenth and twentieth centuries" --